Floating Rate Securities and Immunization: Some Further Results - Morgan, George Emir (Journal of Financial and Quantitative Analysis, 1986)
This article examines the interest rate risk characteristics of a general class of floating rate securities, which includes Chance's securities as a special case. The calculation of duration for Chance's securities is zero, as it should be. Securities in the broader class can have durations that are negative or longer than the period of time that must elapse before the payments can reflect changes in market interest rates. The effect on duration of changes in the parameters of the function relating interest rate shocks to the payments and changes in the slope of the term structure are examined.